The Influence of Leadership Style on the Work Motivation of Health Workers in Regional General Hospitals: Literature Review - Cicih, Lilis Heri Mis; Natasia; Fardiansyah, Haerurahman; Ajwan (Jurnal Kesehatan Masyarakat Perkotaan, 2026)
Health workers are a key resource in hospital service systems, and their work motivation directly affects the quality of healthcare services. Low work motivation among health workers may lead to decreased performance, increased burnout, and higher turnover rates. One of the organizational factors that plays an important role in shaping work motivation is leadership style. This article aims to analyze the influence of leadership styles on the work motivation of health workers in Regional General Hospitals (Rumah Sakit Umum Daerah [RSUD]) through a literature review approach. A narrative literature review was conducted by searching for open-access scientific articles in Google Scholar, PubMed, DOAJ, and the Garuda Portal. The inclusion criteria covered original research articles published between 2015 and 2025, discussing the relationship between leadership style and the work motivation of health workers in the RSUD context and available in full text. A total of five selected articles were analyzed and synthesized thematically. The findings indicate that effective ward leadership, democratic/participative leadership, and achievement-oriented leadership are positively associated with nurses' work motivation in RSUD. In contrast, leadership that provides limited staff involvement does not support optimal work motivation. This review concludes that strengthening communicative, participative, and empowering leadership is an important strategy for improving health workers' motivation and supporting service quality in Regional General Hospitals. Therefore, hospital management is recommended to strengthen leadership capacity through training, supportive supervision, and leadership practices that encourage the active involvement of health workers in decision-making.